2021 European Society of Hypertension practice guidelines for office and out-of-office blood pressure measurement. Issue 7 (July 2021) - Stergiou, George S.; Palatini, Paolo; Parati, Gianfranco; O'Brien, Eoin; Januszewicz, Andrzej; Lurbe, Empar; Persu, Alexandre; Mancia, Giuseppe; Kreutz, Reinhold
Abstract : Collaborators: Lucas Aparicio (Argentina), Kei Asayama (Japan), Roland Asmar (France), Grzegorz Bilo (Italy), Jean-Marc Boivin (France), Alejandro de la Sierra (Spain), Eamon Dolan (Ireland), Jan Filipovsky (Czech Republic), Geoffrey Head (Australia), Yutaka Imai (Japan), Kazuomi Kario (Japan), Anastasios Kollias (Greece), Efstathios Manios (Greece), Klaus Matthias (Germany), Richard McManus (UK), Anastasia Mihailidou (Australia), Paul Muntner (USA), Martin Myers (Canada), Teemu Niiranen (Finland), Angeliki Ntineri (Greece), Takayoshi Ohkubo (Japan), Aleksander Prejbisz (Poland), Athanase Protogerou (Greece), Menno Pruijm (Switzerland), Aletta Schutte (Australia), Daichi Shimbo (USA), Joseph Schwartz (USA), James Sharman (Australia), Andrew Shennan (UK), Jan Staessen (Belgium), Markus van der Giet (Germany), Liffert Vogt (The Netherlands), Jiguang Wang (China), Paul Whelton (USA), William White (USA). Abstract : Supplemental Digital Content is available in the text